Longitudinal patterns of problematic computer game use among adolescents and adults—a 2‐year panel study. (15th July 2014) - Scharkow, Michael; Festl, Ruth; Quandt, Thorsten
Abstract Aims To investigate the longitudinal patterns (stability and change) of problematic computer game use and its interdependencies with psychosocial wellbeing in different age groups. Design Three‐wave, annual panel study using computer‐assisted telephone surveys. Setting Germany. Participants A total of 112 adolescents aged between 14 and 18 years, 363 younger adults between 19–39 years and 427 adults aged 40 years and older (overall n = 902). Measurements Problematic game use was measured with the Gaming Addiction Short Scale (GAS), which covers seven criteria including salience, withdrawal and conflict. Additionally, gaming behaviour and psychosocial wellbeing (social capital and support, life satisfaction and success) were measured in all three panel waves. Findings The generally low GAS scores were very stable in yearly intervals [average autocorrelation across waves and age groups: r = 0.74, confidence interval (CI) = 0.71, 0.77]. Only nine respondents (1%, CI = 0.5, 1.9) consistently exhibited symptoms of problematic game use across all waves, while no respondent could be classified consistently as being addicted according to the GAS criteria. Changes in problematic gaming were not related consistently to changes in psychosocial wellbeing, although some cross‐lagged effects were statistically significant in younger and older adult groups. Conclusions Within a 2‐year time‐frame, problematic use of computer games appears to be a less stable behaviour than reported previously and not related systematically to negative changes in the gamers' lives.